Bilateral variation of forearm flexor muscles - A case report and clinical significance - D Malar; Hemamalini (Wolters Kluwer Medknow Publications, 2012)
During routine dissection, bilateral multiple variations of forearm flexor muscles were observed in a male cadaver. The variations were a) an additional belly arising from the coronoid process of ulna, distal to the origin of ulnar head of flexor digitorum superficialis, passing deep to flexor digitorum superficialis and joining the tendon of flexor digitorum profundus to the middle finger; b) an additional belly arising from the distal part of flexor carpi ulnaris and passing superficial to ulnar nerve and ulnar vessels in the Guyon's canal and c) the origin of second lumbricals from the profundus tendon in the carpal tunnel. An aberrant muscle may stimulate a ganglion or a soft tissue tumor or if in close proximity to a nerve, it may cause pressure neuritis. Identification of these variations is important in defining the anatomical features for clinical diagnosis and surgical procedures.